Successful Combination Therapy with Phototherapy and Topical Corticosteroid in a Rare Case : 57 Years Old Male Patient with Lichen Amyloidosis - Sambodo, Shelly Lavenia; Mawardi, Prasetyadi; Tansil, Ivana; Dewi, Ayu Kusuma; Utama, Rahmat Firdaus Dwi; Octarica, Stella Gracia; Adjie, Sugih Primas (Masters Program in Public Health, Sebelas Maret University, 2024)
Background: : Lichen Amyloidosis (LA) is one of the most common forms of primary localized cutaneous amyloidosis, with clinical manifestations of itchy blackish brown hyperkeratotic papules. The most predilection site is the upper extensor of the legs. This case report aims to improve the clinician’s knowledge regarding clinical features and supporting examinations to the provision of appropriate therapy in LA. Case Report: A 57 years old farmer presented to dermatology and venereology outpatient clinic of Dr. Moewardi general hospital with itchy black spots on nearly all over his body since 2 years ago. Dermatology examination obtained generalized papules and scaly hyperpigmented patches. Dermoscopy revealed a scar-like center with a whitish color in the center. Histopathological examination showed an amorphous eosinophilic (amyloid) in the dermis. Congo red examination demonstrated a reddish-orange amyloid. We treated the patient with oral cetirizine 10 mg/day, desoximetasone 0.25% cream applied twice a day in the morning and in the evening, Carmed® cream 20% cream applied twice a day in the afternoon and night, phototherapy 350 MJ/cm2 twice a week. We observed for 14 weeks. The lesion and itching started improving in week 8. Result: Lichen amyloidosis is resulted from amyloid deposits in the papillary dermis which are derived from degradation of basal keratinocytes. The diagnosis is based on history taking, clinical examination, dermoscopy and skin biopsy. The combination of phototherapy and topical corticosteroid can be an option for LA therapy, especially for the symptom of pruritus. Conclusion: Lichen Amyloidosis is the most common type of primary localized cutaneous amyloidosis, presents as blackish brown hyperkeratotic papules. The combined therapy of topical corticosteroids and phototherapy can significantly improve pruritus and skin lesions.